Inside Indonesia's Mathematics Classrooms : A TIMSS Video Study of Teaching Practices and Student Achievement - World Bank (World Bank, 2012)
The following report is the first of a two-stage video study to examine teaching practices and activities in Indonesian classrooms. The first stage is linked to results of the 2007 Trends in International Mathematics and Science Study (TIMSS) where 100 of the 150 classes that participated in the TIMSS examination also participated in this additional video study component. The second stage will also involve 100 classes that will participate in the 2011 exam. The second phase will follow the same methodology, allowing for comparison across years, but will also involve more in-depth analysis of the links between teaching practices and student outcomes and how teaching practices are influenced by teachers' belief systems and subject content knowledge. Indonesia has been a committed participant in the TIMSS, Program for International Student Assessment (PISA) and the Progress in International Reading Literacy Study (PIRLS) international standardized student examinations for many years and is one of the few non-OECD (Organization for Economic Cooperation and Development) countries to participate so fully. Indonesian student performance in these examinations has been relatively low, even when taking socio-economic levels into account. For example, for mathematics Indonesia ranked 36th out of 48 participating countries in TIMSS 2007, and its score of 397 was more than one standard deviation below the international average (Mullis et al, 2008). The results have been useful in providing an indication of Indonesia's relative standing in student achievement and its progress over time, but the real challenge is to take the next step and translate the results into an understanding of the factors leading to the test scores and what might be done to enhance student achievement in Indonesia.